Private Higher Education in Taiwan: From Prosperity to Adversity - Hou, Angela Yung Chi; Lu, I-Jung Grace (International Higher Education, 2023)
Demographic changes, underenrollment, the COVID outbreak, and growing geopolitical tensions pose many challenges to the private higher education (PHE) sector in Taiwan. This article discusses the state’s governance model relating to the underenrolled PHE sector and analyzes the pluralist-market oriented strategies adopted by semielite private institutions, in a context of local and global competition.